PENGEMBANGAN WISATA HUTAN ADAT IMBO PUTUI DI DESA PETAPAHAN KECAMATAN TAPUNG - Rika Enjelina Simatupang; Mayarni (Halu Oleo University, 2023)
The first customary forest in Riau to receive state recognition was the Imbo Putui Forest. In Petapahan village, customary forests are managed according to their customs. Adat is the standard rule of the Petapahan community in regulating and utilizing the climate. Imbo's customary forest potential is very likely to be developed. The purpose of this research is to describe tourism development and the factors that hinder the development of Imbo Putui customary forest tourism. Cooper's development theory consists of four parts institutional, accessibility, amenity, and attractiveness. This type of research is descriptive. This study found that the development of the Imbo Putui customary forest has been carried out, but has not been optimal. The planned activities are going well, but the development is not done properly, such as facilities and accessibility. As well as the inhibiting factors. The budget that hinders development requires a long process and the lack of human resources to participate in the development of customary forests is an obstacle